Re-emergence of genotype G9 during a five-and-a-half-year period in Turkish children with rotavirus diarrhea. - Gulendam Bozdayi; Aylin Altay; Takaaki Yahiro; Sharnali Ahmed; Melda Meral; Bora Dogan; Bedia Dinc; Ayc a Yeniaras; Yildiz Dallar Bilge; Kamruddin Ahmed (2016)
This study was done to understand the dynamics of rotavirus genotype distribution in Turkish children. Samples were collected from January 2006 through August 2011 from children at a hospital in Ankara. Rotavirus was detected in 28 % (241/889) of the samples. Genotype G9P[8] was predominant (28 %), followed by G1P[8] (16.3 %) and G2P[8] (15.9 %). G9 was absent in the samples from 2006 and 2007 and then re-emerged in 2008 and increased gradually. Phylogenetic analysis showed that Turkish G9 rotaviruses of the present study formed a sublineage with strains from Italy and Ethiopia, possibly indicating spread of a clone in these countries